FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PROFITABILITAS EKUITAS (Studi pada UKM di Kota Pekalongan) - Murtini Murtini (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2012)
The purpose of this study was to obtain empirical evidence about the effect of profit margin, total asset turnover and equity multiplier effect on profitability of equity. The research was conducted on SMEs Pekalongan. The variables used include the dependent variable is financial performance of equity proxied by profitability, and independent veriabel which include profit margin, total asset turnover and equity multiplier. The method of analysis used in this study is multiple regression analysis, beginning with the classic test assumptions include normality test, test and test multikolenieritas heteroscedasticity. The following results are the first results of hypothesis testing can be seen that the variable PM produces t value of 2.944 with a significance value of 0.016 which is significant value less than 0.05 (5 percent). This means that H1 is accepted. As for the second hypothesis examines generate t count each of 1.758 with a significance value of 0.113 is greater than 5%, this means that H2 is rejected. Similarly for the third hypothesis testing bring out t count 0.887 with a significance level of 0.398 is greater than 5%, this means that H3 is rejected. Testing Results simultaneously generate F value of 3.124 and significance value of 0.08. Due to the significant value of less than 0.10 (Î± = 10 percent), it can be concluded that H0 is rejected and Ha accepted. The Adjusted R-square value of 0374 or 37.4%. This means that 37.4 percent of the variation in profitability of equity that can be explained by the variation of the three independent variables, namely profit margin, total asset turnover dan equity multiplier